Psychiatric adverse drug reactions in the paediatric population. Issue 8 (14th February 2020) - Ekhart, Corine; Vries, Tjalling de; Hunsel, Florence van
Abstract : Objective: Due to lack of information on drug use in children, many drugs are used off-label in paediatrics. Increased knowledge of adverse drug reactions (ADRs) would enable a better risk–benefit analysis. Our aim was to characterise drugs causing psychiatric ADRs in children by conducting a descriptive study based on pharmacovigilance reports. Design: Reports submitted to the Netherlands Pharmacovigilance Centre Lareb from 2003 to 2016 were used to investigate drugs causing psychiatric ADRs in the Dutch paediatric population. These data were corrected for drug utilisation in order to correct the number of reports for the number of users of a drug. Main outcome measures: ORs were calculated as a measure of disproportionality for drug–ADR associations for three different age groups. Significant drug–ADR associations were checked if it was labelled in the product information. Results: Lareb received 918 reports of psychiatric ADRs, which constitute 15% of the reports of ADRs in children. Drugs used for the treatment of ADHD (methylphenidate and atomoxetine) and drugs used for the treatment of asthma (montelukast and fluticasone) were the most frequently reported. However, psychiatric ADRs were also reported for less often prescribed medications such as oxybutynin and isotretinoin. Conclusions: Real-world data on psychiatric ADRs in the Dutch paediatric population show a consistent pattern with what is known from drug labels and the literature. Reports of psychiatric ADRs should be taken seriously because of the impact on medication adherence and the well-being of the child and its family.